Is Women's Problematic Pornography Viewing Related to Body Image or Relationship Satisfaction?. Issue 4 (2nd October 2018) - Borgogna, Nicholas C.; Lathan, Emma C.; Mitchell, Ariana
Abstract: Pornography viewing is a growing practice that has been understudied in samples of women. As an answer to calls within the literature, we explored the role of problematic pornography viewing constructs, body image, and relationship satisfaction in a sample of women ( n = 949). Structural equation modeling indicated pornography viewing frequency, perceptions of excessive use, and control difficulties were unrelated to body image or relationship satisfaction. However, problematic pornography use to escape negative emotions significantly predicted participants' body image and relationship dissatisfaction. Future directions, limitations, and clinical implications are discussed.